Calcium-calmodulin-dependent protein kinase mediates the intracellular signalling pathways of cardiac apoptosis in mice with impaired glucose tolerance - Federico, Marilén (2017)
The impact of cardiac apoptosis in pre-diabetic stages of diabetic cardiomyopathy is unknown. We show that myocytes from fructose-rich diet (FRD) animals exhibit arrhythmias produced by exacerbated Ca2+/calmodulin-protein kinase (CaMKII) activity, ryanodine receptor 2 (RyR2) phosphorylation and sarcoplasmic reticulum (SR) Ca2+ leak. We tested the hypothesis that this mechanism also underlies cardiac apoptosis in pre-diabetes.We generated a pre-diabetic model in FRD mice. FRD mice showed an increase in oxidative stress, hypertrophy and systolic dysfunction. FRD myocytes exhibited enhanced SR Ca2+ spontaneous events in the absence of SR Ca2+ load alterations vs. control-diet (CD) myocytes. In HEK293 cells, hyperglycaemia significantly enhanced [3H]ryanodine binding and CaMKII phosphorylation of RyR2-S2814 residue vs. normoglycaemia. CaMKII inhibition prevented hyperglycaemia-induced alterations. FRD also evoked cardiac apoptosis inWT mice vs. CD-WT mice. Co-treatment with the reactive oxygen species scavenger Tempol prevented FRD-induced apoptosis inWT mice. In contrast, FRD enhanced oxidative stress but not apoptosis in FRD-SR-AIP mice, in which a CaMKII inhibitor is targeted to the SR. FRD produced mitochondrial membrane depolarization inWT mice but not in S2814A mice, in which the CaMKII phosphorylation site on RyR2 was ablated. Furthermore, FRD decreased mitochondrial area, mean Feret diameter and mean SR–mitochondrial distance vs. CD-WT hearts. This remodelling was prevented in AC3I mice, with cardiac-targeted CaMKII inhibition. CaMKII phosphorylation of RyR2, SR Ca2+ leak and mitochondrial membrane depolarization are critically involved in the apoptotic pathway of the pre-diabetic heart. The FRD-induced decrease in SR–mitochondrial distance is likely to additionally favour Ca2+ transit between the two organelles.